2016
DOI: 10.1016/j.athoracsur.2015.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercurrent Operation and Cerebral Oxygenation on Developmental Trajectory in Congenital Heart Disease

Abstract: Patient physiologic status assessed by cerebral and somatic near-infrared spectroscopy is associated with ND performance. Incremental surgical procedures are not associated with ND performance when adjusted for cardiopulmonary bypass time and physiologic status. Treatment strategies that target improved physiologic status may also improve ND outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
(35 reference statements)
1
25
0
Order By: Relevance
“…Narrower arterial-cerebral and arterial-somatic saturation by NIRS were associated with better motor performance assessed by the Bayley Scales of Infant Development III 32 . In addition, higher arterial saturation values were associated with improved motor performance scores with age 32 . Future studies will be essential to reach a consensus on the risks and benefits of optical imaging technologies as a management tools to improve neurodevelopmental outcomes in CHD.…”
Section: Neuroimaging In Chdmentioning
confidence: 93%
See 1 more Smart Citation
“…Narrower arterial-cerebral and arterial-somatic saturation by NIRS were associated with better motor performance assessed by the Bayley Scales of Infant Development III 32 . In addition, higher arterial saturation values were associated with improved motor performance scores with age 32 . Future studies will be essential to reach a consensus on the risks and benefits of optical imaging technologies as a management tools to improve neurodevelopmental outcomes in CHD.…”
Section: Neuroimaging In Chdmentioning
confidence: 93%
“…A recent longitudinal study assessed neurodevelopmental outcomes in a large cohort of mixed CHD patients (178 patients) following surgery 32 . Narrower arterial-cerebral and arterial-somatic saturation by NIRS were associated with better motor performance assessed by the Bayley Scales of Infant Development III 32 .…”
Section: Neuroimaging In Chdmentioning
confidence: 99%
“…Therefore, the baseline measurements were performed after the anesthesia induction, similar to other studies. [24] In addition, the small sample size, although consistent with the previous studies reported in the literature, can be deemed as a limitation. However, considering that a 10-unit difference between each group's NIRS values was significant, the power of the study was calculated as 92%.…”
Section: Discussionmentioning
confidence: 72%
“…[23] Cardiopulmonary bypass time, total length of hospital stay, and tube feedings are the main risk factors for abnormal neurodevelopment. [24] However, recent technologies should be carefully reviewed according to diseases and surgeries, and their effectiveness should be supported by evidence to yield satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that PDA leads to lower cerebral oxygenation, 10-12 and Lemmers et al 13 previously reported that infants with PDA had mean arterial blood pressure and regional cerebral oxygen saturation that were significantly lower than those of control infants (mean arterial blood pressure, 33 ± 5 mm Hg vs 38 ± 6 mm Hg; regional cerebral oxygen saturation, 62% ± 9% vs 72% ± 10%, for PDA and controls, respectively). Although lower cerebral oxygenation has been shown to be associated with worse neurodevelopmental outcome in term infants undergoing surgery for congenital heart disease, [14][15][16] this relationship is not addressed in the current article. In preterm infants, lower cerebral volume, specifically decreased total brain volume and deep nuclear gray matter volume, is known to be associated with worse cognitive and motor development and a higher incidence of cerebral palsy.…”
Section: Department Of Pediatrics Section Of Critical Care Baylor Cmentioning
confidence: 82%